Adult men's perception of prostate cancer and its implications for male sexuality (Research, Society and Development, 2022)
Objectives: to analyze the perception of adult men about prostate cancer and the implication of this pathology in male sexuality. Methodology: descriptive, exploratory and qualitative study. Performed at the urology outpatient clinic of a University Hospital in Niterói. For data collection, an individual semi-structured interview was carried out. For the analytical procedure, the method of interpretation of meanings was used, based on hermeneutic-dialectical principles. Results: 15 adult men participated in the study, aged over 50 years with a diagnosis of prostate cancer and who expressed a desire to participate in the research. The testimonies show that the changes that occurred due to prostate cancer affect men with regard to their sexuality. Final Considerations: the care provided by nursing to men, especially in relation to prostate cancer, requires much more than a simple technical skill, it requires professionals to perform a practice committed to the health of the population, aiming at the promotion of health and the disease prevention.